A integração latino-americana: da identidade à estrutura econômica - Figueiredo, Alexandre Ganan de Brites; Gremaud, Amaury Patrick; Braga, Márcio Bobik (Revista USP, 2023)
This article discusses the integrationist project based on its relationship with the concept of “Latin America”. Thus, the evolution of this concept will be addressed since its emergence in the midnineteenth century, still as the expression of an allegedly cultural unit, until its affirmation, by the Economic Commission for Latin America (Cepal), in 1948, as an object of analysis designator of the same economic and historical structure, shared by all countries in the region, despite their particularities. It is intended to demonstrate that it was the process of consolidation of a continental identity that paved the way for the realization of more lasting integration bodies. Finally, the successive waves of integration – and their ebbs – will be discussed in light of the current challenges posed to two old projects: that of the existence of a “Latin American” unit and that of its integration.